2016
DOI: 10.1038/srep24877
|View full text |Cite
|
Sign up to set email alerts
|

Dandruff is associated with the conjoined interactions between host and microorganisms

Abstract: Dandruff is an unpleasant scalp disorder common to human populations. In this study, we systematically investigated the intra- and inter-associations among dandruff, physiological conditions such as sebum of the scalp, host demographics such as gender, age and the region of the scalp, and the microorganisms on the scalp. We found that the physiological conditions were highly relevant to the host age and varied in different regions of the same scalp. The sebum quantity and water content were negatively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
127
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(152 citation statements)
references
References 40 publications
17
127
1
7
Order By: Relevance
“…In our study, we found the most abundant bacteria on the scalp are Propionibacterium and Staphylococcus , concurrent with previous findings . Studies also suggested a reciprocal inhibition between the two main components . The bacterium P. acnes could hydrolyze triglycerides to release free fatty acids and promote bacterial adherence and produce bacteriocins to kill other strain, which might explain our results that the percentage of Propionibacterium was significantly increased in sensitive scalp, with less percentage of other strains and lower diversity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we found the most abundant bacteria on the scalp are Propionibacterium and Staphylococcus , concurrent with previous findings . Studies also suggested a reciprocal inhibition between the two main components . The bacterium P. acnes could hydrolyze triglycerides to release free fatty acids and promote bacterial adherence and produce bacteriocins to kill other strain, which might explain our results that the percentage of Propionibacterium was significantly increased in sensitive scalp, with less percentage of other strains and lower diversity.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, no significant differences were noted on the average dandruff scores between NS and SS, indicating sensitive scalp might have different mechanisms with dandruff. Studies have been suggested the distinction between crown and occiput in biophysical parameters and sensations . Therefore, we performed all the measurements at two sites, crown and occiput.…”
Section: Discussionmentioning
confidence: 99%
“…(Clavaud et al, 2013; Wang et al, 2015). More recently, Xu et al (2016) showed that host factors such as skin sebum and water content are related to dandruff. Analyzing scalp microbiome by NGS, the authors found that dandruff is more closely related to bacteria than to fungi, and reported no significant association with Malassezia at species level, although some OTUs showed positive or negative correlation with dandruff (Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Xu et al (2016) showed that host factors such as skin sebum and water content are related to dandruff. Analyzing scalp microbiome by NGS, the authors found that dandruff is more closely related to bacteria than to fungi, and reported no significant association with Malassezia at species level, although some OTUs showed positive or negative correlation with dandruff (Xu et al, 2016). Our results corroborate the relationship between dandruff and bacteria but not with Malassezia at species level, and showed for the first time increased diversity and dissimilarity among dandruff samples, affecting also asymptomatic skin sites.…”
Section: Discussionmentioning
confidence: 99%
“…Corynebacterium spp., Streptococcus spp., Acinetobacter spp., and Prevotella spp. are listed among other significantly less numerous species . Some discrepancies between studies have also been presented; for example, Perez‐Perez et al .…”
Section: Composition Of the Microbiome On The Scalp Surface And In Tementioning
confidence: 99%